Psikoedukasi untuk Mengurangi Kecemasan pada Tahanan di Rutan Kelas Iia Yogyakarta: Penelitian - Ika Wahyu Pratiwi; A’yunin Akrimni Darojat; Kumala Windya Rochmani; Farida Agus Setiawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to address anxiety among inmates at Yogyakarta Class IIA Detention Center by providing psychoeducation on anxiety management. The main issue identified was the lack of knowledge about how to cope with anxiety caused by waiting for legal sentencing, separation from family, and negative thoughts. The intervention involved interviews, observations, mental health screenings, and the implementation of psychoeducational activities and practical anxiety management techniques. Twenty-three male inmates participated, with anxiety levels screened using the DASS-211 tool. Results showed significant improvement in both anxiety understanding and management. Before the intervention, 100% of the participants experienced severe anxiety. Post-intervention, 26% reached normal levels, while those with very high anxiety levels decreased to 52%. The study concludes that ongoing support for anxiety management is essential and suggests further programs to enhance the inmates' psychological well-being.